16 September, 04:31

# My math teacher said: I provided you with an already simplified expression. Your task is to create two expressions (for each) that would simplify the given expression.3x - 19-11y + 625h - 4262w + 80-17b + 1

+2
1. 16 September, 06:47
0
1. (4 x - 20) - (x + 1) = 3 x - 19

2. (-6 y + 3) + (-5 y + 3) = - 11 y + 6

3. (15 h - 50) + (10 h + 8) = 25 h - 42

4. (60 w + 40) + (2 w + 40) = 62 w + 80

5. (20 b + 10) - (37 b + 9) = -17 b + 1

Step-by-step explanation:

The one good way to simplify the given expression is to break the TERMS from all the given terms and take it out of the given expression.

(a) 3 x - 19

Here, two expressions that on simplification gives 3 x - 19 are A - B

Here A = 4 x - 20, B = x + 1

A - B = (4 x - 20) - (x + 1) = 3 x - 19

(b) - 11 y + 6

Here, two expressions that on simplification gives - 11 y + 6 are A + B

Here A = - 6 y + 3, B = - 5 y + 3

A + B = (-6 y + 3) + (-5 y + 3) = - 11 y + 6

(c) 25 h - 42

Here, two expressions that on simplification gives 25 h - 42 are A + B

Here A = 15 h - 50, B = 10 h + 8

A + B = (15 h - 50) + (10 h + 8) = 25 h - 42

(d) 62 w + 80

Here, two expressions that on simplification gives 62 w + 80 are A + B

Here A = 60 w + 40, B = 2 w + 40

A + B = (60 w + 40) + (2 w + 40) = 62 w + 80

(e) - 17 b + 1

Here, two expressions that on simplification gives 3 x - 19 are A - B

Here A = 20 b + 10, B = 37 b - 9

A - B = (20 b + 10) - (37 b + 9) = -17 b + 1

Here, there MANY WAYS TO DO THIS, i am just giving one.